Comparative study of Brachypodium distachyon and kazakhstan soft wheat varieties resistance to Puccinia recondita (ҚазҰУ Хабаршысы. Биология сериясы, 2019)
One of the important issues of the modern world economics is ensuring the quality of food, relevant for Kazakhstan, where the possibility of cultivating soft and hard wheat varieties and high technological quality grain production are among the strategically important tasks of its national security. Biotic and abiotic environmental stress factors may lead to decrease in cereals productivity, and annual loss in the global yield of crops from diseases, according to FAO, is estimated at more than $25 billion, equivalent to 35% of the potential harvest.  At the same time, creation of pathogen-resistant varieties of cultivated plants by means of traditional breeding is long-term, and the evolution of pathogens is ahead of the possibilities of practical breeding, resulting in creation of pathogen resistant varieties being late with their introduction into production; for a deeper understanding of the basics and in terms of accelerating processes in the leading countries of the world, model organisms are involved into the process.  The aim of this work is to estimate the influence of brown leaf rust on the elements of productivity and protein content in grain of local varieties of soft wheat Kazakhstanskaya 19, Kazakhstanskaya early and new model object Brachypodium distachyon along with their correlation. The results of the comparative study of the impact of biotic stress on the elements of productivity have shown that Puccinia recondita statistically significantly reduces the productivity of all parameters in wheat varieties Kazakhstanskaya 19, Kazakhstanskaya early and model object Brachypodium distachyon. The protein content in the grain of wheat of local breeding varieties Kazakhstanskaya 19, Kazakhstanskaya early and wild cereal Brachypodium distachyon is not changed when infected with brown leaf rust.Key words: Brachypodium distachyon, Kazakhstani soft wheat varieties, brown leaf rust, resistance, study.